Displacement of hypersonic boundary layer instability and turbulence through transpiration cooling - Kerth, P; Le Page, LM; Wylie, S; Ravichandran, R; Ceruzzi, A; Williams, BAO; McGilvray, M (AIP Publishing, 2024)
Hypersonic boundary-layer transition onset is commonly characterized in wind tunnel experiments by measuring the surface heat transfer rise above the laminar level. Techniques such as infrared thermography and thin film gauges are routinely used in the field. However, when an interfering cooling effect is present due to foreign gas transpiration, these methods are known to be inadequate. This study uses a 7° half-angle cone at Mach 7 with helium or nitrogen injection through a porous segment within the model frustum. The injector spans 60° in azimuth and is located 300 mm from the sharp nose tip, close to the onset of natural boundary-layer transition. Nitrogen and helium injection reduce the surface heat flux below the laminar level for up to 50 mm downstream of the injector. Comparisons to schlieren images and pressure measurements indicate an advance of transition. Optical diagnostics reveal how instabilities are pushed away from the model surface by the injected gas. This is found through spectral analysis of schlieren images and focused laser differential interferometry signals, which revealed further information about how inaccuracies of detecting transition with surface gauges under the influence of transpiration cooling originate.